Wear mechanisms of different engineering systems under higher solicitations: Overview and case studies. (December 2018) - Sellami, Amira; Hentati, Nesrine; Kchaou, Mohamed; Kus, Recai; Elleuch, Riadh; Chowdhury, Mohammad Asaduzzaman
Abstract: Today's, vehicle systems and components require more interaction and innovation in mechanical systems. Furthermore, mechanical components should ensure by its properties the required functionalities. Potentially, under service, those systems are able to cause severe accidents. The particular attention is according to the improving requirements engineering in the choice of the material especially for automotive components submitted to higher stress level (induced by mechanical, thermal, tribological solicitations). Wear phenomena play a huge role in the effectiveness and durability of the vehicle system. The understand of wear as a failure mechanism induced by coupling and transient phenomena are fundamental in an innovative and creative process to improve automotive performance. Three cases of wear reported by the automotive industries are discussed in the text above: case 1: axle shaft of a motor vehicle, case 2: synchronizer rings, case 3: brake lining material. Highlights: Cases studies of engineering systems of automotive parts are appraised. Different wear mechanisms are reported Different methods must be used leading to modify the composition or the tribological characteristics of the components.